Correlation between Serum Progesterone Level on the Day of Ovulation Trigger During In vitro Fertilization and Its Effect on Treatment Outcome - Nagaraja, N (J Hum Reprod Sci, 2019)
BACKGROUND: Premature luteinization (PL) is defined as a premature rise in serum progesterone concentration on or before the day of ovulation trigger with human chorionic gonadotropin. The incidence of PL varies between 5% and 30% during in vitro fertilization and embryo transfer (IVF-ET). MATERIALS AND METHODS: The prospective observational study comprising 380 patients undergoing IVF-ET. Blood samples were collected for serum progesterone level estimation on the day of ovulation trigger. Ovum pickup was done 36 h later and serum progesterone levels were correlated with IVF-ET outcome. STUDY OUTCOME: To correlate serum progesterone level on the day of ovulation trigger during IVF and its effect on treatment outcome. RESULTS: Mean serum progesterone level in the positive pregnancy group and negative pregnancy group was 0.892 ± 0.752 ng/ml and 0.91 ± 0.688 ng/ml, respectively (P = 0.961). The overall incidence of PL was 12.8% with 12.7% and 13.6% in the agonist and antagonist protocol respectively (P = 0.9001). PL incidence was 13.5% and 13.4% in positive pregnancy and negative pregnancy group (P = 0.223). CONCLUSION: PL has been associated with 12.8% of the IVF cycles. There was no statistically significant difference observed in the incidence of PL between different IVF stimulation protocols. PL does not seem to affect IVF outcome.